Culture et formation de l'esprit chez K. Popper et J.S. Bruner - Alain Firode (Nantes Université, 2016)
Bruner often refers to Popper's famous theory of "world 3" in order to underline the major role which, according to him, cultural and social environment plays in development of human mind. Bruner's conceptions, nevertheless, are different from Popper's. Their disagreement mainly originates in the fact that Bruner doesn't share the realistic conception of symbolic world which Popper supports. In addition, the psychologist assumes a structural difference between narrative and scientific logics, which contradicts some basic principles of popperian epistemology. The result is that Popper's and Bruner's theories of mind show different pedagogical implications